2019
DOI: 10.1186/s40246-019-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

Translating pharmacogenomics into clinical decisions: do not let the perfect be the enemy of the good

Abstract: The field of pharmacogenomics (PGx) is gradually shifting from the reactive testing of single genes toward the proactive testing of multiple genes to improve treatment outcomes, reduce adverse events, and decrease the burden of unnecessary costs for healthcare systems. Despite the progress in the field of pharmacogenomics, its implementation into routine care has been slow due to several barriers. However, in recent years, the number of studies on the implementation of PGx has increased, all providing a wealth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 84 publications
1
106
0
Order By: Relevance
“…Variations in genes that encode proteins involved in drug pharmacokinetics and pharmacodynamics lead to interindividual heterogeneity in drug response and can greatly affect clinical outcome. Dosage guidelines have been developed by organizations such as the Clinical Implementation of Pharmacogenetics Consortium (CPIC; cpicpgx.org) to aid physicians in incorporating pharmacogenetics into their practice, however the adoption of pharmacogenetics by practicing physicians has been slow 2,3 . Doctor's may not directly be using pharmacogenetics to inform practice, but genetics influences how patients respond to drugs nonetheless.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in genes that encode proteins involved in drug pharmacokinetics and pharmacodynamics lead to interindividual heterogeneity in drug response and can greatly affect clinical outcome. Dosage guidelines have been developed by organizations such as the Clinical Implementation of Pharmacogenetics Consortium (CPIC; cpicpgx.org) to aid physicians in incorporating pharmacogenetics into their practice, however the adoption of pharmacogenetics by practicing physicians has been slow 2,3 . Doctor's may not directly be using pharmacogenetics to inform practice, but genetics influences how patients respond to drugs nonetheless.…”
Section: Introductionmentioning
confidence: 99%
“…As accurate inference of metabolic activity of CYP2D6 cannot currently be done from GWAS chip data alone, the copy-number imputation method creates new opportunities for development towards and research of individualized medicine. When more data emerge, the pharmacogenetic decision algorithms can be then fine-tuned to reflect newest findings 54 . Hence, it is important that pharmacogenetic reports can be updated to maintain best possible dosing guidelines available for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…practice guidelines that can assist providers in applying the results of PGx testing to the management of medications used to treat mood disorders, cardiovascular disease, cancer, or other diseases among adults. 2,3 Previous research in adult populations has demonstrated the clinical utility [4][5][6][7][8] and cost-effectiveness 9,10 for both reactive PGx testing to guide current treatment and pre-emptive testing to guide future treatment decisions. However, the evidence base for PGx testing in pediatric patients and in treatment of diseases prevalent during childhood is less robust.…”
Section: Pharmacogenetic Testing In Childrenmentioning
confidence: 99%